TRAINING AND ASSISTANCE FOR MENTAL HEALTH CADRES IN IMPROVING KNOWLEDGE AND SKILLS OF FAMILY OF ODGJ PATIENTS IN THE MANGASA COMMUNITY HEALTH CENTER, MAKASSAR CITY - Maryati Tombokan; Sri Angriani; Naharia Laubo; Subriah Subriah (Bajang Institute, 2022)
Puskesmas as a first-level service facility that can provide mental health services for the community is very important, especially in monitoring families in increasing the coverage of mental treatment for patients with schizophrenia in their work area where data is found for relapses of schizophrenia patients because the coverage of mental patients who do not seek treatment regularly is found to be 51.1% do not seek treatment regularly (Riskesdas 2018). The limited ability of families and the community, especially in understanding the care of patients with ODGJ (People With Mental Disorders), this is due to the diversity of population characteristics based on demographics, both in terms of education, age, gender, culture and occupation, which can affect different knowledge and perceptions about patients. with mental disorders. Purpose: The purpose of community service activities is to improve the skills of family members, mental health cadres in identifying and recognizing signs and symptoms of mental disorders in people with mental disorders in the community and how to provide care and treatment as well as follow-up in terms of providing health services. referral through the mangasa health center and then forwarded to a mental hospital as the right hospital in handling mental patients, especially for ODGJ patients. Methods: consisting of a pre test, providing training materials and followed by a post test to identify the level of knowledge and skills of cadres in early detection of family members identified as ODMK or ODGJ by using the mentoring process in using the cadre pocket book that has been given. Results: After being given training and the process of mentoring and guidance, most of the respondents' knowledge and skills are getting better, especially in increasing their ability to carry out early detection to identify family members who are at risk of suffering from mental disorders (ODMK) and recognize the signs and symptoms of family members who suffer from mental disorders. soul (ODGJ) using the format provided. Conclusion: With training and mentoring mental health cadres can improve the knowledge and skills of families in caring for ODGJ patients in the Mangasa Health Center area of ​​Makassar City. Suggestion: For mental health cadres who have been trained, it is hoped that they can disseminate information, knowledge and skills about early detection of family members who are at risk of mental health problems (ODMK) and can identify signs and symptoms of ODGJ patients in the community.